2016
DOI: 10.1016/j.abb.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cardiomyopathy mutation (R97L) in mouse cardiac troponin T on the muscle length-mediated recruitment of crossbridges is modified divergently by α- and β-myosin heavy chain

Abstract: Hypertrophic cardiomyopathy mutations in cardiac troponin T (TnT) lead to sudden cardiac death. Augmented myofilament Ca2+ sensitivity is a common feature in TnT mutants, but such observations fail to provide a rational explanation for severe cardiac phenotypes. To better understand the mutation-induced effect on the cardiac phenotype, it is imperative to determine the effects on dynamic contractile features such as the muscle length (ML)-mediated activation against α- and β-myosin heavy chain (MHC) isoforms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Hypertrophic cardiomyopathy (HCM) mutations in the central region (CR; residues 80–180) of cardiac troponin T (TnT) are not well tolerated, perhaps because of their negative impact on thin filament cooperativity and length-dependent activation of cardiac myofilaments. Previous work from our laboratory has demonstrated that the structural integrity of CR is important for thin filament cooperativity and length-dependent activation of cardiac myofilaments ( Ford et al, 2012 ; Gollapudi and Chandra, 2016a , b ). Recent studies have suggested that impairment of length-dependent activation may be one of the primary mechanisms by which HCM mutations lead to altered cardiac phenotype and deleterious complications associated with HCM ( Sequeira et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertrophic cardiomyopathy (HCM) mutations in the central region (CR; residues 80–180) of cardiac troponin T (TnT) are not well tolerated, perhaps because of their negative impact on thin filament cooperativity and length-dependent activation of cardiac myofilaments. Previous work from our laboratory has demonstrated that the structural integrity of CR is important for thin filament cooperativity and length-dependent activation of cardiac myofilaments ( Ford et al, 2012 ; Gollapudi and Chandra, 2016a , b ). Recent studies have suggested that impairment of length-dependent activation may be one of the primary mechanisms by which HCM mutations lead to altered cardiac phenotype and deleterious complications associated with HCM ( Sequeira et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the R131W mutation in TnT may perturb CR-Tm interactions to modulate XB recruitment dynamics. Given that the TnT-mediated function is dependent on the myosin heavy chain (MHC) isoform (Ford et al, 2012 ; Chandra et al, 2015 ; Gollapudi et al, 2015 ; Gollapudi and Chandra, 2016 ), we hypothesized that the effects of DCM-linked mutations in TnT on contractile dynamics would be differently modulated by α- and β-MHC. To better understand the molecular mechanisms that lead to contractile dysfunction, especially in relevance to humans, it is important to consider the differential impact of α- and β-MHC isoforms on contractile dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the molecular mechanisms that lead to contractile dysfunction, especially in relevance to humans, it is important to consider the differential impact of α- and β-MHC isoforms on contractile dynamics. This is because previous studies have demonstrated that the effects of cardiomyopathy mutations in TnT on steady-state and/or dynamic contractile features are differently modulated by α- and β-MHC isoforms (Ford et al, 2012 ; Chandra et al, 2015 ; Gollapudi et al, 2015 ; Gollapudi and Chandra, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings support the TnC A8V mutation disrupts muscle function by altering the TnC-TnI interaction and provide further support for the significance of this interaction in the myofilament regulation of cardiac contraction. Work from the laboratory of Murali Chandra sought to investigate the myofilament mechanism responsible for differential phenotypes observed for the TnT R97L hypertrophic cardiomyopathy linked mutation (12). Mechanic measurements of R97L TnT muscles containing α- or β-myosin heavy chain (MHC) demonstrated that while the R97L mutation increased calcium sensitivity similarly in the presence of both the α- or β-MHC, cross-bridge recruitment was dependent upon the MCH isoform co-expressed.…”
mentioning
confidence: 99%